2002
DOI: 10.1063/1.1445417
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the axisymmetric core-annular flow. II. The less viscous fluid in the core, saw tooth waves

Abstract: The nonlinear dynamics of the concentric, two-phase flow of two immiscible fluids in a circular tube is studied when the viscosity ratio of the fluid in the annulus to that in the core of the tube, μ, is larger than or equal to unity. For these values of the viscosity ratio the perfect core-annular flow (CAF) is linearly unstable and it is necessary to keep the ratio of the thickness of the annulus to the radius of the tube small so that the solutions remain uniformly bounded. The simulations are based on a ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Sahu et al 37 showed that the above system becomes absolutely unstable for a certain range of parameters and have indicated the region of absolute and convective instabilities in the Reynolds number and viscosity ratio space. There are also several investigations 29,30,[38][39][40][41][42][43][44][45][46][47][48] not relevant to the present study (but worth mentioning in the present context) that deals with stability characteristics of viscosity stratified flows in rigid channels/pipes, involving the displacement of one fluid by another. The interesting features and the type of instabilities displayed by these flow systems with boundaries as either rigid walls or rigid circular pipes suggest that it is worth analyzing the analogous flow systems in configurations with velocity slip at the boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al 37 showed that the above system becomes absolutely unstable for a certain range of parameters and have indicated the region of absolute and convective instabilities in the Reynolds number and viscosity ratio space. There are also several investigations 29,30,[38][39][40][41][42][43][44][45][46][47][48] not relevant to the present study (but worth mentioning in the present context) that deals with stability characteristics of viscosity stratified flows in rigid channels/pipes, involving the displacement of one fluid by another. The interesting features and the type of instabilities displayed by these flow systems with boundaries as either rigid walls or rigid circular pipes suggest that it is worth analyzing the analogous flow systems in configurations with velocity slip at the boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found. [24][25][26][27][28] In neutrallybuoyant core-annular pipe flows, d'Olce et al 29 observed axisymmetric "pearl" and "mushroom" patterns at high Schmidt number.…”
Section: Introductionmentioning
confidence: 99%
“…These have included linear stability analyses for horizontal [6,7,[17][18][19] and vertical pipes [5,20], accounting for viscosity and density contrasts, experiments [21,22] and numerical simulations in straight [9,10,23] and corruagated pipes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of investigations have focused on the stability of immiscible fluids (see, for instance, [1,[4][5][6][7][8][9][10] and references therein). Starting with the work of Yih [4] and Hickox [5], carried out using long-wave theory in planar channels and cylindrical pipes, respectively, these studies have shown that two-layer flows are destabilized linearly by an 'interfacial' mode at arbitrarily small Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%